Efficiency of plant growth regulators application in onion napiform (Allium сера L.) cultivation from seeds - Л. П. Музика (Plant Varieties Studying and Protection)
Results of research on application of plant growth regulators in cultivation of Onion Napiform from seeds in non-irrigated grain-vegetable crop rotation of Northeast Forest-steppe of Ukraine. Efficiency of seeds presowing damping was established, in the solutions of preparations Baikal EM and Emistim С and in the solution of preparation Emistim С for double use - of seeds presowing damping and of plants spraying in 5-6 leaves phase.